Implementasi Implementasi penilaian autentik dan portofolio dalam pembelajaran pendidikan Islam di MTsN 1 Kota Padang - Mifta Nola Septia; Jaslainy Jaslainy; Sufrizal Sufrizal; Muhamad Husin; Sri Wahyuni (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Assessment is an essential component in Islamic education as it serves to measure students' competence comprehensively, encompassing attitudes, knowledge, and skills. Authentic assessment and portfolios are relevant evaluation approaches for assessing students' abilities in real and continuous contexts. This study aims to describe and analyze the implementation of authentic assessment and portfolios in Islamic education at MTsN 1 Kota Padang, as well as to identify the advantages and challenges encountered in their application. The research employed a qualitative approach with a field study design. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative methods. The results indicate that authentic assessment and portfolios have been implemented through various learning activities, such as worship practice, evaluation of religious attitudes, project assignments, and collections of student work. The application of these assessments provides a more comprehensive picture of students' learning development and aligns with Islamic values, including honesty, responsibility, and consistency. However, its implementation still faces challenges, particularly related to limited time and teachers’ administrative workload. Overall, authentic assessment and portfolios have the potential to enhance the quality of Islamic education at MTsN 1 Kota Padang if supported by optimal planning and management.